2015
DOI: 10.1002/pssa.201532614
|View full text |Cite
|
Sign up to set email alerts
|

From thermoelectric bulk to nanomaterials: Current progress for Bi2Te3 and CoSb3

Abstract: Bi2Te3 and CoSb3 based nanomaterials were synthesized and their thermoelectric, structural, and vibrational properties analyzed to assess and reduce ZT‐limiting mechanisms. The same preparation and/or characterization methods were applied in the different materials systems. Single‐crystalline, ternary p‐type Bi15Sb29Te56, and n‐type Bi38Te55Se7 nanowires with power factors comparable to nanostructured bulk materials were prepared by potential‐pulsed electrochemical deposition in a nanostructured Al2O3 matrix. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…6b ), reaching a maximum of 209 μV K −1 in Bi 0.5 Sb 1.5 Te 3 at 395 K, as checked in several samples. Pristine Bi 2 Te 3 is an n-type semiconductor, with Seebeck-coefficients in the range −50 to −260 μV K −1 17 , 36 , 37 . The literature indicates that as Bi 3+ is progressively replaced by Sb 3+ , the sign of the conduction carriers becomes positive, reaching a maximum value 250 μV K −1 at 320 K 35 , 38 , for bulk samples prepared by mechanical alloying and SPS, corresponding to a nominal composition of Bi 0.5 Sb 1.5 Te 3 .…”
Section: Resultsmentioning
confidence: 99%
“…6b ), reaching a maximum of 209 μV K −1 in Bi 0.5 Sb 1.5 Te 3 at 395 K, as checked in several samples. Pristine Bi 2 Te 3 is an n-type semiconductor, with Seebeck-coefficients in the range −50 to −260 μV K −1 17 , 36 , 37 . The literature indicates that as Bi 3+ is progressively replaced by Sb 3+ , the sign of the conduction carriers becomes positive, reaching a maximum value 250 μV K −1 at 320 K 35 , 38 , for bulk samples prepared by mechanical alloying and SPS, corresponding to a nominal composition of Bi 0.5 Sb 1.5 Te 3 .…”
Section: Resultsmentioning
confidence: 99%
“…In bismuth telluride samples, charge carriers concentration is strongly affected by antisite Bi Te and Te Bi defects, which are randomly created during synthesis process. This feature yields a wide range of Seebeck coefficient values measured in samples prepared by different methods [15,[34][35][36][37][38][39].…”
Section: Bi 2 Tementioning
confidence: 95%
“…Thermal conductivity contains both lattice and electronic parts; k = k l +k e , k l is lattice thermal conductivity relative to lattice vibrations (phonon), and k e is electronic thermal conductivity related to electronic structure. Over the last many years, intensive research has been done to increase ZT for high thermoelectric performance [8][9][10][11][12][13][14][15][16][17]. It was previously reported that graphene and boron nitride have very high formation energy.…”
Section: Introductionmentioning
confidence: 99%